2019
DOI: 10.1149/2.0911910jes
|View full text |Cite
|
Sign up to set email alerts
|

Dual Atmosphere Isothermal Aging and Rapid Thermal Cycling of Ag-Ni and Ag-CuO Stainless Steel to Zirconia Braze Joints

Abstract: Silver-copper oxide brazes are commonly used to bond zirconia to stainless steel (SS) for Solid Oxide Fuel Cell (SOFC) and other high temperature joining applications. In fact, conventional Ag-CuO compositions (where Cu segregates to the surface, oxidizes, and reduces the silver wetting angle on zirconia from ∼85 to ∼40°) allow brazing to be performed in air. Unfortunately, the relatively high ∼40°wetting angles of these reactive air brazes, and the ability of SOFC anode gases to reduce the CuO in them, produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…According to the XRD patterns shown in Figure b and the elemental distribution in Figure d, it can be considered that the metal-side oxide consists of two layers: the (Cu, Cr, Fe) 3 O 4 layer (close to Ag) and the Cr 2 O 3 -rich layer (close to AISI 441). The previous studies on the RAB of stainless steel also reported similar oxide layers. …”
Section: Resultsmentioning
confidence: 52%
“…According to the XRD patterns shown in Figure b and the elemental distribution in Figure d, it can be considered that the metal-side oxide consists of two layers: the (Cu, Cr, Fe) 3 O 4 layer (close to Ag) and the Cr 2 O 3 -rich layer (close to AISI 441). The previous studies on the RAB of stainless steel also reported similar oxide layers. …”
Section: Resultsmentioning
confidence: 52%
“…In these applications, electrical contacts with low electronic sheet resistance, low electronic contact resistance, and high adhesion strength are desired. Recently, a new Particle-Interlayer-Directed Wetting and Spreading (PIDWAS) technique has been developed that utilizes a) the low wetting angle of silver on nickel (10,11), and b) the high work of adhesion between nickel and various oxides (12), to fabricate well-adhered silver patterns on substrates not normally wet by silver (5,(13)(14)(15)(16)(17)(18). However, the full electrical performance (i.e.…”
Section: Introductionmentioning
confidence: 99%